Injury prevention in marathon runners - Nathan, J. (Journal of Outdoor Activities, 2013)
More people run today than ever before with participation in marathons becoming increasingly popular. Injury rates in those training for a marathon can be as high as 90%. 89 individuals running for Arthritis Research UK were followed up before and after running the London Marathon. All were asked to complete two online questionnaires, one before the marathon asking for demographic information, previous history of running injury and training habits and one after regarding how the run went and recovery time. The mean response rate across both surveys was 62%. There is a significant association between time and injury whilst running the London Marathon (p = 0.003). This is supported by the fewest percentage of runners who sustained an injury are those who ran the marathon in less than 4 hours (13%). This report indicates how difficult it is to determine who will sustain an injury whilst running a marathon. It highlights that they are many risk factors for incurring injury but few proven by scientific research. It does suggest a relationship between marathon time and injury. There is a need for guidelines for all marathon runners to help reduce injury.